Pemanfaatan Refrigerasi Tenaga Surya untuk Menjaga Mutu Hasil Tangkapan Nelayan - Rahmad Hadi; Apih Suparlin; Dian Sutono; Terry Yuliardi (Jurnal Airaha, 2019)
Keeping all catches is an important part of fishing activities after catching with the aim of maintaining catches that have high selling prices. Good handling of fish after the ship is taken is one way to get good results. Handling can be in the form of maintaining the temperature of the catch. Regarding to the results of the 2017 applied research carried out related to ships and fishing gear in the coastal Karawang district, it is denied that fisheries in this area are generally very low in terms of the production of fish caught which is poor quality provided direct impact on the sale price of the catch. Based on this, an easy cooling engine is needed that does not burden the operations. Therefore the purpose of this study is to make a solar powered refrigeration unit (solar energy), knowing the performance of a mini refrigeration unit that has been made (COP) and finds out the quality of fish stored in accordance with organoleptic observation. The results showed that the mini refrigeration units made worked well with performance (COP) of 3.51 mean mini refrigeration units that have a good efficiency above 1. Moreover, the fish quality was stored in the mini-refrigerators had organoleptic values ​​according to the standard food is an average of 8.